(untitled) (Bangladesh Journal of Neuroscience, 2018)
Background: The diagnosis of Extra Pulmonary Tuberculosis, especially tubercular meningitis (TBM) is challenging due to frequent atypical clinical presentation, inadequate clinical sample, and paucibacillary nature of the biological samples, which frequently results in a delay or deprivation of treatment. A semi quantitative, nested, real time PCR Gene-Xpert test is showing promising result in diagnosing pulmonary TB diagnosis, but its role in TBM is yet to be validated. Methods: It was a cross sectional observational study carried out on 40 clinically suspected TBM patients admitted in neuromedicine, medicine and pediatric medicine at CMCH. Clinical, radiological evaluation and conventional tests were done before PCR (Gene-Xpert) using cerebrospinal fluid. Results: The mean age of the study population was 28.59 (±16.87) years. Seventeen (42.5%) were male and 23 (57.5%) were female with a male to female ratio of 1:1.35. Out of 40 study cases AFB was presesnt in direct microscopy in only 1(2.5%) case, positive growth on culture in 5 (12.5%) cases and positive Gene-Xpert test in 9 (22.5%) cases. Sensitivity, specificity, PPV, NPV and diagnostic accuracy of Gene-Xpert (PCR) was 44.44%, 96.77%, 80%, 85.71%, and 85.0% respectively considering culture as gold standard. Sensitivity of Gene-Xpert in CSF was 22.5% as compared to culture which was only 12.5 % among the study cases. Conclusion: PCR (Gene-Xpert) is highly sensitive and speed in diagnosis of TBM compared to conventional methods. Bangladesh Journal of Neuroscience 2018; Vol. 34 (1): 1-8